(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article discusses the topic of the bicultural personality of the future translator, the relevance of which is due to the growing importance of intercultural communication and the need to train specialists who are able to work effectively in the context of globalization. The author analyzes the role of translators in the modern world, their tasks and requirements, as well as the peculiarities of working with different cultures and languages.